Interacting neutrinos in cosmology: exact description and constraints - Oldengott, Isabel Mira; Rampf, Cornelius (Journal of cosmology and astroparticle physics, 2017)
We consider the impact of neutrino self-interactions described by an effective four-fermion coupling on cosmological observations. Implementing the exact Boltzmann hierarchy for interacting neutrinos first derived in [1] into the Boltzmann solver CLASS, we perform a detailed numerical analysis of the effects of the interaction on the cosmic microwave background (CMB) anisotropies, and compare our results with known approximations in the literature.
Gesehen am 04.09.2018